PERAN MEKANISME CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN REPUTASI KANTOR AKUNTAN PUBLIK ATAS MANAJEMEN LABA (Media Riset Akuntansi, 2022)
This study aims to determine and analyze the effect of corporate governance mechanisms (institutional ownership, managerial ownership, independent commissioners, and audit committees), firm size, and the reputation of public accounting firms on earnings management as proxied by discretionary accruals. The population in this study were 56 mining companies listed on the Indonesia Stock Exchange in 2015-2018. The sampling technique used was purposive sampling method, so as many as 14 samples were obtained. This study uses multiple linear regression analysis using the SPSS 24 program. The results show that managerial ownership has a significant positive effect on earnings management. Meanwhile, institutional ownership, independent board of commissioners, audit committee, firm size and reputation of public accounting firm have no significant effect on earnings management.